Integrasi Literasi Informasi dalam Kurikulum: Pendekatan Informed Learning - Kiramang, Khaeruddin; Rusanda, Arman (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to analyze the implementation of information literacy based on “informed learning” in order to integrate library services into the education curriculum at schools/madrasahs and higher education institutions in Indonesia. The discussion begins by examining Indonesian National Library Regulations Number 4 of 2024 and Number 5 of 2024, both of which emphasize the importance of libraries as integrated learning resource centers. Through a literature review, it was found that information literacy serves as a foundation for learners to identify, access, evaluate, and process information responsibly. Using the “informed learning” approach, which highlights the active involvement of learners in reflection and collaboration, information literacy is not taught as a standalone subject but is integrated and intertwined with academic content. This practice is enriched by research- and inquiry-based learning models, support from digital technology, and close collaboration among librarians, teachers, and lecturers. However, challenges such as limited infrastructure, human resource competencies, and uneven policy implementation remain obstacles. On the other hand, cross-institutional collaborative opportunities, the use of open resources, and formal curriculum adjustments can enhance the effectiveness of information literacy in improving educational quality. The results of this study recommend strengthening human resource capacity, incorporating technology, and conducting ongoing evaluations so that the integration of information literacy through “informed learning” can genuinely reinforce the learning ecosystem in Indonesia.